RASIONALITAS PETANI DALAM MEMPERTAHANKAN LAHAN PERKEBUNAN KARET DI DESA DUSUN TUO KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Nora Permaisari; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted in Dusun Tuo Village, Kuantan Hilir District, Kuantan Singingi Regency. The purpose of this study was to determine: 1) Socio-economic conditions of rubber farmers 2) The reasons for farmers to maintain rubber plantations in Tuo Hamlet Village, Kuantan Hilir District, Kuantan Singingi Regency. Researchers used descriptive quantitative methods. The population in this study were all rubber farmers who own as well as cultivators in Dusun Tuo Village totaling 179 and the sample in this study was 50% of the total population, which amounted to 64 people. Sampling in this study using simple random sampling technique. The data instruments are observation, questionnaire, and documentation. Based on the results of the study, it can be concluded that the socio-economic conditions of the farmers in the average age of the garden range from 20-29 years with a percentage of 45.31%, income is relatively low, namely 62.50%. The land area is classified as low, namely 0.5-0.9 Ha with a percentage of 45.31%, the dry season and rainy season plantation yields of farmers' rubber plantations are classified as low at 42.19%. Meanwhile, 71.88% on average have their own house and 54.69% type of permanent house. The reason for surviving is to avoid risk because 68.8% have been working on rubber since 10-30 years, 92.9% of farmers do not have spare land, and 89 ,1% of farmers do not have other businesses besides rubber farming. The rationality of farmers to survive in rubber plantations because 57.8% of access to markets affects transportation costs. Limited capital, including the cost needed, seeds, and land area are one of the reasons farmers stay in rubber plantations, 76.6% of farmers are willing to turn their land into rubber plantations if they have more than 2 hectares of land. Keywords : Rationality, Farmer, Rubber Plantation.